2016
DOI: 10.1021/acssuschemeng.6b00451
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and Nitrogen Codoped Graphene with Inserted Carbon Nanospheres as an Efficient Bifunctional Electrocatalyst for Oxygen Reduction and Evolution

Abstract: It is highly desirable but remains challenging to develop efficient bifunctional electrocatalysts for both the oxygen reduction and oxygen evolution reactions (ORR/OER) in rechargeable metal–air batteries and unitized regenerative fuel cells. Herein, we developed a facile and cost-effective strategy to prepare a cobalt and nitrogen codoped three-dimensional (3D) graphene catalyst through inserting carbon nanospheres into the interlayers of graphene sheets. The catalyst exhibited not only excellent ORR performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…[117,[119][120][121] Other than the carbon-based nanomaterials, MoS 2 has also been reported that its edges are preferred sites for O 2 chemisorption. Generally, Co 3+/4+ and Ni 3+/4+ are known as active centers to incorporate with graphene for enhanced OER and ORR performance.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[117,[119][120][121] Other than the carbon-based nanomaterials, MoS 2 has also been reported that its edges are preferred sites for O 2 chemisorption. Generally, Co 3+/4+ and Ni 3+/4+ are known as active centers to incorporate with graphene for enhanced OER and ORR performance.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[128] Copyright 2014, American Chemical Society. [119] Copyright 2016, American Chemical Society. a,d) TEM image of Co-N-GCI.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…have been widely reported due to their excellent bifunctional oxygen electrode activity. For instance, Co nanoparticles (NPs) and N‐codoped 3D graphene were synthesized via thrusting carbon nanospheres into the interlayers of graphene nanosheets and exhibited superior bifunctional oxygen electrode activity (Δ E = 0.81 V) . Very recently, Deng's group constructed an efficient and stable bifunctional oxygen electrode catalyst (Δ E = 0.80 V) by anchoring Fe NPs on N‐doped nanocarbon‐intercalated graphene .…”
Section: Introductionmentioning
confidence: 99%
“…Then, FeCo alloy NPs adhered on the inside wall of N‐doped carbon nanotubes were prepared by Ci and co‐workers and achieved a peak power density of 152 mW cm −2 in rechargeable Zn–air battery . This is because porous carbon materials typically possess excellent conductivity and rich porous structure, and thereby can facilitate the transfer of electrons and prevent the agglomeration of transition metal NPs . In addition, it was demonstrated that doping porous carbon materials with transition metal and nitrogen can form more effective active catalytic sites and further enhance the bifunctional catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as a result of the global energy crisis and environmental pollution, the search for cheap, efficient, and environmentally friendly alternative energy conversion and storage systems has aroused huge and sustained interest [1,2]. Hydrogen is a clean energy source, and fuel cells are the best way to utilize it.…”
Section: Introductionmentioning
confidence: 99%